Performance testing of an innovative integrated zenithal daylight guide with solar water heater under real-weather conditions - Mahmoud Eid El-saggan; Ahmed Rekaby; Walid Aniss Aissa; Ahmed M. Reda (Next Energy)
Zenithal Daylight Guides (ZDG) and Solar Water Heaters (SWH) are individual energy-saving solutions utilized across diverse building types. This study proposes an innovative integrated power-saving system, uniting ZDG and SWH into a single model. The integration concept is rooted in leveraging the available space surrounding the daylighting device's pipe to incorporate a solar heater via a serpentine collector. The primary aim of this amalgamation is to optimize solar energy savings, minimize spatial demands, and alleviate manufacturing expenses. Moreover, the impetus behind this study stems from the recent emergence of daytime power outages in Egypt, attributed to heightened consumption surpassing production capacities. The ZDG is still not well known in Egypt. This is the only study until the year 2022/2023 in Aswan, Egypt, that analyzes the performance of this device under extreme sunlight conditions (with maximum global illumination reaching approximately 118 Klux). Across various seasons, the lighting and thermal efficacy of the current model underwent experimental testing and analysis to assess its practical utility. The integrated system effectively elevated the water temperature and achieved adequate light transmission, as indicated by the obtained results. The average transmitted indoor illumination on the work surface reached approximately 2470 lux. The reliance on electrical lighting could be mitigated for up to 5 hours. On the other hand, the highest water temperature and maximum instantaneous efficiency reached are about 70°C and 37%, respectively. Throughout the experiments, the proposed solar heater achieved a maximum daily thermal efficiency of 31.5%. The findings are deemed satisfactory and promising.